2013
DOI: 10.1002/jgrb.50242
|View full text |Cite
|
Sign up to set email alerts
|

Application of real‐time GPS to earthquake early warning in subduction and strike‐slip environments

Abstract: [1] We explore the application of GPS data to earthquake early warning and investigate whether the coseismic ground deformation can be used to provide fast and reliable magnitude estimations and ground shaking predictions. We use an algorithm to extract the permanent static offset from GPS displacement time series and invert for the slip distribution on the fault plane, which is discretized into a small number of rectangular patches. We developed a completely "self-adapting" strategy in which the initial fault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 78 publications
(88 reference statements)
1
60
0
Order By: Relevance
“…Based on the measurement of the static field, the GPS-based approaches (Allen and Ziv, 2011;Colombelli et al, 2013) can potentially provide valid slip estimate upon the arrival of S waves. However, with limited spatial resolution and the smoothing regularization applied in the inversion, the boundary of the actual slip area can be only roughly defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the measurement of the static field, the GPS-based approaches (Allen and Ziv, 2011;Colombelli et al, 2013) can potentially provide valid slip estimate upon the arrival of S waves. However, with limited spatial resolution and the smoothing regularization applied in the inversion, the boundary of the actual slip area can be only roughly defined.…”
Section: Discussionmentioning
confidence: 99%
“…Among the ongoing efforts to determine the finite-fault extent in real time, Global Positioning System (GPS) approaches provide more reliable static displacements, and thus a static slip model, than seismic methods (Hudnut et al, 2002;Allen and Ziv, 2011;Colombelli et al, 2013). The FinDer approach is also proposed to determine linear fault geometry based on the difference in near/far-field seismic waveforms, provided dense station coverage (Böse et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Real-time GNSS data with high sampling (e.g., 1 Hz) possibly enable us to rapidly estimate the earthquake size and its expansion (i.e., coseismic fault model) that can more directly relate to the generated tsunami than the conventional point source estimation based on seismic wave analysis alone (Blewitt et al 2006;Ohta et al 2012;Wright et al 2012;Colombelli et al 2013). For the case of near-coast great tsunamigenic earthquakes, these GNSS analyses possibly work well to obtain a reliable fault model within about 10 min.…”
Section: Open Accessmentioning
confidence: 99%
“…For the first issue, the 2011 Tohoku earthquake (M9.0) showed that rapid estimation of source parameters is hampered by very large focal areas and the simultaneous occurrence of aftershocks (Hoshiba et al 2011;Hoshiba and Ozaki 2013). Attempts to solve the problem of large focal areas have included analysis of real-time GNSS data (e.g., Colombelli et al 2013;Grapenthin et al 2014) and direct estimation of focal area and rupture direction directly from observed seismograms (Böse et al 2012). Other ingenious methods have been proposed to distinguish simultaneous multiple earthquakes (e.g., Tamaribuchi et al 2014;Wu et al 2014).…”
Section: Introductionmentioning
confidence: 99%